2013
DOI: 10.1038/jcbfm.2013.175
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis of Lipid-Phase-Continuity Proton Transfer for Aerobic ATP Synthesis

Abstract: The basic processes harvesting chemical energy for life are driven by proton (H þ ) movements. These are accomplished by the mitochondrial redox complex V, integral membrane supramolecular aggregates, whose structure has recently been described by advanced studies. These did not identify classical aqueous pores. It was proposed that H þ transfer for oxidative phosphorylation (OXPHOS) does not occur between aqueous sources and sinks, where an energy barrier would be insurmountable. This suggests a novel hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Treatment of whole cells with resveratrol for some days partly restored the Fanconi anaemia mitochondrial metabolic activity while decreasing oxygen uptake in wild‐type cells (Columbaro et al ., ). The effects of N,N_‐dicyclohexylcarbodiimide and oligomycin are different as they act on the F o moiety in the lipid phase (Morelli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Treatment of whole cells with resveratrol for some days partly restored the Fanconi anaemia mitochondrial metabolic activity while decreasing oxygen uptake in wild‐type cells (Columbaro et al ., ). The effects of N,N_‐dicyclohexylcarbodiimide and oligomycin are different as they act on the F o moiety in the lipid phase (Morelli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The fact that platelets do not contain a double‐membrane system similar to that of mitochondria, where to accumulate protons, may seem to represent a conceptual difficulty in the hypothesis about an ectopic OXPHOS metabolism conduction. However, an H + delivery at the centre of a membrane expressing the electron transfer chains [Morelli et al., ], which has found many experimental confirms [Cherepanov et al., ; Mulkidjanian, ], would apply also to platelets. Notably, it was reported that, in a mitochondrion, the free protons are too few to sustain the ATP synthase activity [Bal et al., ] and that the ΔpH across the inner mitochondrial membrane is low [Żurawik et al., ] and opposite with respect to that supposed by the chemiosmotic theory [Tupper and Tedeschi, ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the structural function, CL is required for the enzymatic activity of complex II, where one CL molecule is located near the binding site for ubiquinone, suggesting that CL is involved in the proton pumping mechanism. A role for CL in proton transport has been recently proposed also for complex IV [171]. In cellular models of BTHS, including patient-derived iPSC, oxygen consumption at the respiratory chain is reduced, reflecting the impaired activity of individual respiratory chain complexes and diminished energetic coupling between complexes [148,154,156].…”
Section: Mitochondrial Disordersmentioning
confidence: 99%